Harnessing new models of care for chronic disease: co- design and sustainable implementation of group clinics into UK clinical practice. (2019) - Birrell, Fraser; Goff, Iain; Coulson, Liz; Jones, Tania; Baqir, Wasim; O'Brien, Nicola; Rapley, Tim; Gray, Keith; Flood, Brian; Russell-Westhead, Michele
No abstract available